Association between albumin-corrected calcium and all-cause mortality in patients with heart failure: a retrospective study - Yao, Xiongda; Leng, Yurong; Cao, Junda (Frontiers in Cardiovascular Medicine, 2025)
BackgroundHeart failure (HF), a global health challenge, is a leading cause of mortality in hospitalized patients. Early and accurate prognostic evaluation in these patients is vital for guiding clinical management. Our aim was to explore the association between albumin-corrected calcium (ACC) and mortality in hospitalized patients.MethodsThis retrospective cohort study utilized data from the Medical Information Mart for Intensive Care IV (MIMIC-IV) database. Patients were stratified into three groups based on ACC levels. The association between ACC and clinical outcomes in HF patients was analyzed using Cox proportional hazards regression and restricted cubic spline models.ResultsA total of 4,737 heart failure patients were included. Multifactorial Cox regression revealed that elevated ACC levels were significantly associated with increased 30-day and 180-day mortality. Restricted cubic spline analysis demonstrated a U-shaped relationship between ACC levels and mortality, with an inflection point at 9.18. Patients with ACC levels above 9.18 exhibited an 20.4% higher risk of 30-day mortality [Hazard ratio (HR): 1.204, 95% (Confidence interval) CI: 1.009–1.437] and a 20.8% higher risk of 180-day mortality (HR: 1.208, 95% CI: 1.019–1.431) compared to those with ACC below 9.18.ConclusionsThe observed U-shaped association between ACC levels and 30- and 180-day mortality in HF patients highlights the potential utility of ACC as a prognostic marker.